2018
DOI: 10.5334/egems.259
|View full text |Cite
|
Sign up to set email alerts
|

The Imperative for Patient-Centered Clinical Decision Support

Abstract: This commentary introduces the Patient-Centered Clinical Decision Support (PCCDS) Learning Network, which is collaborating with AcademyHealth to publish “Better Decisions Together” as part of eGEMs. Patient-centered clinical decision support (CDS) is an important vehicle to address broad issues in the U.S. health care system regarding quality and safety while also achieving better outcomes and better patient and provider satisfaction. Defined as CDS that supports individual patients and their care givers and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…Shared-decision-making between patients and clinicians can be seriously compromised without effective mechanisms to aid understanding of benefits and risks for outcome probabilities. Research in clinical decision support has shown that their use can reduce costs, improve quality of care and reduce medical errors in clinical settings [60].…”
Section: Effects Of the Cdsss In The Populationmentioning
confidence: 99%
“…Shared-decision-making between patients and clinicians can be seriously compromised without effective mechanisms to aid understanding of benefits and risks for outcome probabilities. Research in clinical decision support has shown that their use can reduce costs, improve quality of care and reduce medical errors in clinical settings [60].…”
Section: Effects Of the Cdsss In The Populationmentioning
confidence: 99%
“…The specific needs of different stakeholders have to be considered, e.g. patients and their healthcare professionals, EHR vendors and Standard Developing Organizations (SDOs), as well as healthcare policymakers [63].…”
Section: Success Factors For the Implementation Of Cdsssmentioning
confidence: 99%
“…CDSSs are multifaceted and incorporate individualized patient recommendations through information technology algorithms enhancing clinical decision-making skills. [29][30][31][32] CDSS alerts can also evaluate and improve metric performance. 33 These algorithms can facilitate cancer screening recommendations based on a patient's individualized health risk and comorbidities, to guide the provider on specific orders.…”
Section: Clinical Decision Support Systemsmentioning
confidence: 99%